Peningkatan Keterampilan Berbicara pada Mahasiswa S1 PGSD Unismuh Makassar: Tantangan dan Solusi dalam Pembelajaran - St.Zulaikha Hidayat; Besse Syukroni Baso (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This article discusses improving speaking skills in undergraduate PGSD students at Muhammadiyah University of Makassar (Unismuh Makassar), especially in Advanced Indonesian Language Learning courses. This research aims to identify the challenges faced by students in improving their speaking skills and propose solutions that can be applied in the learning process. The method used is qualitative research with a case study approach, which involves observation, interviews and document analysis. The research results show that the main challenges faced by students are lack of self-confidence, limited vocabulary, and the inability to organize arguments systematically. The proposed solutions include the application of effective communication techniques, the use of technology-based learning media, and the habit of speaking in public to increase self-confidence. It is hoped that this research can make a positive contribution to the development of speaking skills of PGSD students at Unismuh Makassar, as well as becoming a reference for teaching Indonesian in tertiary institutions.